(untitled) (L’uomo nero. Materiali per una storia delle arti della modernità, 2023)
Italian artistic relational practices in the Nineties presented peculiar features if related to the more studied international scenario. Like the latter, the first were characterized by the attention to processual and collaborative aspects, and by an unforeseen expansion through time and space. The Italian experiences were also intermixed with political activism and technologies, and sometimes adopted collective names, reacting to the several groups that, in the previous decades, were born responding to economic issues rather than to a common research. This return to conceptual and political practices paved the way to the Disordinazioni, disturbing and unexpected actions that took place in the urban environment, conceived in Rome starting from 1994 by Giuliano Lombardo. The experience was thus followed by the actions led by the group Giochi del Senso e/o non-senso, then renamed Studi Ricerche Contemporanee.